"Of every land the guest": Aubrey de Vere's travels. Issue 2 (2nd April 2016) - Fegan, Melissa
Abstract : The experience of travel, the figure of the traveller, the relationship between landscape and nationality, and a complex attitude towards colonisation are extremely important in the poetry and prose of Aubrey de Vere (1814–1902). Alongside ideas of emigration and exile in the Irish context, the wider intellectual and spiritual significance of travel is explored in poems such as "A Farewell to Naples", "Lines Written Under Delphi", or "A Wanderer's Musings at Rome" and in de Vere's travel book Picturesque Sketches of Greece and Turkey (1850). De Vere's ideal traveller must be hardy, embracing "an emancipation from the bondage of comforts" (1850, vol. 1, 47), and reining in his exuberant Romantic sensibility with careful "management of the mind" (vol. 1, 67) and "moral temperance" (vol. 1, 118). This is very far removed from "that universal nuisance", the Philistine Englishman abroad, of whom he is reminded all too frequently, particularly in Greece and in the Ionian islands, a British protectorate. But de Vere's self-definition against the English traveller begins to unravel in Constantinople, where he embraces a new national identity as a Frank among an alien people. His experiences in the East also redefine his understanding of Ireland as "an Eastern nation in the West" (1863, xiv).